Bermacam-macam Pendidikan Doktor - Sadtono, E., Dr. (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 1981)
This article examines the various types of doctoral education across different countries and the diverse meanings attached to the doctoral degree. Like other academic titles, the doctoral degree has evolved throughout the 20th century and is not confined to medicine, but also extends to other fields, including languages. The paper highlights the distinctions between professional and non-professional doctorates, as well as the differences in doctoral education systems internationally, with particular emphasis on the United States and Europe. In the U.S., doctoral research tends to be more structured, while in other countries, such as Denmark, the systems vary significantly. These differences shape how doctoral degrees are understood, recognized, and valued. The article aims to provide an overview of the variations in doctoral education worldwide and underscores the flexibility of doctoral programs.